Case-Based Learning on Concept Mastery and Students' Thinking Ability in the Field of Nutrition and Health - Desak Made Citrawathi; Putu Budi Adnyana (Universitas Pendidikan Ganesha, 2023)
The nutrition and health lectures show that students can optimally develop higher-order thinking skills. The learning process with the strategies and methods used has yet to be able to maximize the student learning process to be able to develop high-level thinking skills. This study aimed to analyze the effectiveness of case-based learning on students' mastery of concepts and thinking skills in the field of nutrition and adolescent health. This type of research is quantitative. The research subjects were 6th-semester students who programmed the Nutrition and Health Course with 24 people. The research design is one short case study. Methods of data collection using observation and tests. The research instruments used were tests and questionnaires to determine student responses. The results showed that the mean score of students' mastery of concepts about nutrition and health was 86.13, which was classified as very good, while students' thinking skills were obtained at 86.08, which was classified as very good. The student response to the case-based learning was very good, scoring 87.33. The effectiveness of case-based learning is determined based on the effectiveness index obtained by 100%. It was concluded that concept mastery, thinking skills, and student responses were in the very good category, and the effectiveness of case-based learning in adolescent nutrition health studies was also very good.